Process Investigation Perpetrator Action Criminal Terrorism In Indonesia - Rahmah Hayati Sinaga; Yasmirah Mandasari Saragih; Mhd Azhali Siregar; Azhar Hairi Putra; Mohammed Faiz Hadi (International Journal of Law, Crime and Justice, 2024)
Terrorism is Wrong one crime Which outside normal Because has creating terror creates fear and that's scary has the impression of being cruel to groups or groups. The crime of terrorism has taken away rights basic para human victim Which No know anything about the origin , causes and the purpose of acts of terrorism. Because in in carrying out their actions perpetrators of this terrorism t is indiscriminate. This action is completely contrary to Article 3 Universal Declaration of Human Rights (UDHR) or Universal Declaration of Human Rights (UDHR) Which sounds "Every person entitled on life, freedom and security as an individual”, Article 6 paragraph (1) ICCPR ( International Covenant on Civil and Political Right ) 1999 which states "Every human being is entitled to the inherent right to life himself and every other person must not be deprived of his life arbitrarily", Article 28 A of the 1945 Constitution of the Republic of Indonesia which reads "Everyone has the right to live and the right to defend their life and existence" and Article 28 G paragraph (1) which reads "Everyone has the right to personal protection, family, honor, dignity, property under his control and has the right to a sense of security and protection from the threat of fear of doing or not doing something which is a human right.” This research aims to know How arrangement investigative law t act criminal terrorism in Indonesia And What obstacle investigator in do investigation t act criminal terrorism in Indonesia. This research uses normative legal research research ingredients literature To use get ingredients form theories, concepts, principles as well as regulation law Which related with role investigator in process handling follow criminal terrorism.